SOLUTION AND ANALYSIS OF THERMAL ELASTOHYDRODYNAMIC LUBRICATION MODEL FOR TOOTH AND SLIDING RING COMBINED SEAL - ZHANG Yi; YANG Qiang; YANG Lin; WANG HaiJuan; XIONG ZiJie; XIONG SiYang; ZHONG SiPeng (Jixie qiangdu)
Combined with the high pressure and high temperature working condition and the characteristics of tooth and sliding ring combined seal, the mathematical model of the rotating slip ring type combined seal is established based on the theory of thermoelastic hydrodynamic lubrication. Furthermore, the elastic deformation of the tooth and sliding ring combined seal under the action of oil film pressure is obtained by the matrix method of deformation influence coefficient based on the theory of small deformation. Combined with the hydrodynamic lubrication equation, the temperature field energy equation and the viscosity temperature equation, the finite difference method is used to solve the thermoelastic flow pressure lubrication model. The oil film thickness distribution and oil film pressure distribution in the working process of the combined seal ring of the toothed slip ring are calculated by MATLAB. The results show that the roughness of the ring has a significant effect on the sealing performance. The film pressure increases first and then decreases in the axial direction, and fluctuates in the stable range in the circumferential direction.Moreover, the oil film thickness and pressure of the sealing ring decrease with the increase of the ambient temperature.